KONSEP NEGARA IDEAL PERSPEKTIF ABU A’LA AL-MAUDUDI - Akmal; Djafar, Usman (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
Abu A'la al-Maududi is an accomplished speaker and a very productive writer, especially in the field of religion. In this connection it is important to always observe Abu A'la's views related to politics, the state, and Islam. Not much different from other thinkers. Abu A'la is a great thinker of Islam who is very well known in the Islamic world. Pakistan, more than any Islamic country, faces more interesting problems in its struggle to get its Islamic identity. Since the establishment of an Islamic state in 1947, the Pakistani nation has tried to show its importance in its existence. And the first choice fruit presents two types of modern Islamic states namely Maulana Abu A'la Maududi, a founder of a political organization (Jama'ati Islam) proposing a more traditional theocratic state form, while Fazlur Rahman a professor of Islamic studies from Cambridge University who is also the director of the Islamic Study Board who has the support of the government, provides an overview of a more modern Islamic state based on popular sovereignty. Although in the past Pakistan declared itself to be a Republican state, there was no one that had ever been compiled to implement Islam.